New postcranial elements of the Thalassodrominae (Pterodactyloidea, Tapejaridae) from the Romualdo Formation (Aptian–Albian), Santana Group, Araripe Basin, Brazil. (5th August 2013) - Aires, Alex S. S.; Kellner, Alexander W. A.; Müller, Rodrigo T.; Da Silva, Lúcio R.; Pacheco, Cristian P.; Dias‐Da‐Silva, Sérgio; Angielczyk, Kenneth
Abstract Tapejarids are edentate pterosaurs recovered mainly from Early Cretaceous deposits. They are diagnosed by five synapomorphies, among which only one is postcranial: a broad and well‐developed tubercle at the ventroposterior margin of the coracoid. Regarding the clade Thalassodrominae, most phylogenetic studies are based on cranial elements, as postcranial skeletons of these pterosaurs are rare. Here, new postcranial material from the Romualdo Formation (Aptian–Albian) from the Araripe Basin is described. The material comprises the three posteriormost cervical vertebrae, the first seven dorsal vertebrae (fused into a notarium), both scapulocoracoids, a fragment of a sternum, a partial right humerus, a small fragment of a 4th phalanx of the wing finger, a distal extremity of the right femur and the proximal portions of both tibia and fibula. Comparisons with other specimens and morphological features examined in a phylogenetic context, such as the presence of three foramina lateral and dorsal to the neural canal of the cervical vertebrae, the presence of a notarium and a pneumatic foramen on the ventral side of the proximal portion of the humerus, allow the assignment of this specimen as Thalassodrominae indet. Regarding palaeobiogeographical aspects, to date, this clade is exclusively found in the Romualdo Formation. It is the most complete postcranial material assigned to the Thalassodrominae described so far.